Testing the contributions of outside directors: should family firms respond differently? - Mesnik , Samy Sznajder; Gama , Marina Bahia Amado; Carneiro, Jorge Manoel (Review of Business Management, 2023)
Theoretical framework – Based on agency theory and its derivatives, we capture the specificities of family firms relative to non-family firms. Design/methodology/approach – Drawing from an extensive and updated database of over 370 publicly listed companies in Brazil, this study conducted panel data regressions with fixed effects on three different response variables, in order to have a broader perspective and reduce the bias of the results. Moreover, we performed robustness tests with different measurement methods. In addition, we tested the selection of variables by addressing both internal and external validity criteria, in addition to convergent and nomological validity, according to the literature. Findings – The empirical results indicate that there is a relationship between board independence and short-term financial performance for a cohort of family firms. Practical & social implications of research – This research contributes to various stakeholders by providing relevant insights about an important ESG criterion, which opens up a path for further studies. Originality/value – This is a novel approach to relevant phenomena from the perspective of family firms compared to non-family firms. Also, this paper deepens the study of family businesses and considers different cohorts of firms. Keywords - Corporate Governance, Family Firms, Outside Directors, Firm Performance, Emerging Markets.